Pengaruh Pembelajaran Digital Terhadap Hasil Belajar Siswa - Anisah Anisah; Syahid Suhandi Aziz; Ferdian Arie Bowo (Postgraduate of Jayabaya University, 2021)
The purpose of this research was to identify the effect of digital learning on student learning outcomes. Digital learning creates learning situations for students in discussion and enhances online interactive learning with teachers. The population of this study were fifth grade students at SDIT Al Bariyah Jakarta. The findings show that there is an effect of digital learning on student learning outcomes. Digital learning has been shown to have an influence on student learning outcomes. Suggestions in this study indicate that the promotion of digital learning can provide an alternative to teaching innovation in the classroom. With the advancement of information technology and relevant technology, digital learning will be accepted by students and teachers.